Linear psoriasis/Lichen striatus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2021)
Among the acquired diseases which are distributed along Blaschko’s lines there are linear psoriasis and lichen striatus: in addition to the same distribution, which is linked to a condition of mosaicism, they are both acquired inflammatory diseases and usually asymptomatic, sometimes creating problems of differential diagnosis.